The Interprocessual-Self Theory in Support of Human Neuroscience Studies - Luis, Elkin O.; Akrivou, Kleio; Bermejo-Martins, Elena; Scalzo, Germán; Orón, José Víctor (Frontiers in Psychology, 2022)
Rather than occurring abstractly (autonomously), ethical growth occurs in interpersonal relationships (IRs). It requires optimally functioning cognitive processes [attention, working memory (WM), episodic/autobiographical memory (AM), inhibition, flexibility, among others], emotional processes (physical contact, motivation, and empathy), processes surrounding ethical, intimacy, and identity issues, and other psychological processes (self-knowledge, integration, and the capacity for agency). Without intending to be reductionist, we believe that these aspects are essential for optimally engaging in IRs and for the personal constitution. While they are all integrated into our daily life, in research and academic work, it is hard to see how they are integrated. Thus, we need better theoretical frameworks for studying them. That study and integration thereof are undertaken differently depending on different views of what it means to live as a human being. We rely on neuroscientific data to support the chosen theory to offer knowledge to understand human beings and interpersonal relational growth. We should of course note that to describe what makes up the uniqueness of being, acting, and growing as a human person involves something much more profound which requires too, a methodology that opens the way for a theory of the person that responds to the concerns of philosophy and philosophical anthropology from many disciplines and methods (Orón Semper, 2015; Polo, 2015), but this is outside the scope of this study. With these in mind, this article aims to introduce a new explanatory framework, called the Interprocessual-self (IPS), for the neuroscientific findings that allow for a holistic consideration of the previously mentioned processes. Contributing to the knowledge of personal growth and avoiding a reductionist view, we first offer a general description of the research that supports the interrelation between personal virtue in IRs and relevant cognitive, emotional, and ethic-moral processes. This reveals how relationships allow people to relate ethically and grow as persons. We include conceptualizations and descriptions of their neural bases. Secondly, with the IPS model, we explore neuroscientific findings regarding self-knowledge, integration, and agency, all psychological processes that stimulate inner exploration of the self concerning the other. We find that these fundamental conditions can be understood from IPS theory. Finally, we explore situations that involve the integration of two levels, namely the interpersonal one and the social contexts of relationships.